Liberal democracy and environmentalism : the end of environmentalism? - Wissenburg, M. L. J. (Marcel L. J.); Levy, Yoram, 1967- (Routledge/ECPR studies in European political science, 2004)
In recent decades, environmental issues have increasingly been incorporated into liberal democratic thought and political practice. Environmentalism and ecologism have become fashionable, even respectable schools of political thought. This apparently successful integration of environmental movements, issues and ideas in mainstream politics raises the question of whether there is a future for what once was a counter-movement and counter-ideology. Liberal Democracy and Environmentalism provides a reflective assessment of recent developments, social relevance and future of environmental.